Dampak Pengembangan Pariwisata Dalam Perspektif Masyarakat Desa Adat Canggu, Bali - Wisnu Pramudya; Heddy Shri Ahimsa-Putra; Dyah Widiyastuti (Tulisan Ilmiah Pariwisata (TULIP), 2025)
This study explores the impacts of tourism development from the perspective of indigenous people in Canggu, Bali (a village undergoing rapid transition from agriculture to tourism). As tourism reshapes the physical, socio-cultural, and economic landscape of Canggu, concerns arise over the sustainability of this transformation. Using a qualitative approach, data were gathered through participant observation and in-depth interviews with 17 informants, followed by thematic analysis. Findings indicate that tourism has brought economic benefits such as increased income, new job opportunities, and improved infrastructure. Ownership of accommodation units by many households reflects a relatively equitable distribution of economic gains. However, the shift away from agriculture raises concerns about food security and the erosion of traditional livelihoods. Culturally, tourism has helped revive arts and rituals, yet also risks commodification and altered communal values. Traditions like Ngayah have adapted into more pragmatic forms. Environmentally, residents are worried about land conversion, congestion, pollution, water scarcity, and the existence of irrigation systems like Subak. Weak regulation and declining trust in governance worsen these issues. Despite this, tourism remains widely supported, highlighting a tension between economic benefit and ecological stability. The study calls for community-driven tourism strategy that balances growth with cultural and environmental sustainability.